Praktek Penjualan Akun Ilegal Netflix Oleh Retailer di Marketplace : Telaah Tanggungjawab dan Akibat Hukum - Fransiska Dwi Putri Usman; Mutya Cherawaty Thalib; Mohammad Rivaldy Moha (Journal of Contemporary Law Studies, 2026)
This study aims to examine the forms of legal liability borne by retailers involved in the sale of illegal Netflix accounts in marketplace platforms, as well as to analyze the legal consequences for consumers arising from such practices. The research employs a normative juridical method, utilizing statutory and conceptual approaches. Data are analyzed through deductive reasoning by drawing conclusions from general legal principles to specific cases. The findings reveal that retailers bear legal responsibility toward consumers under the Indonesian Consumer Protection Law, either in the form of breach of contract or unlawful acts as stipulated in the Civil Code. Additionally, retailers may also be subject to both civil and criminal liability under the Copyright Law. The study further demonstrates that marketplace platforms may share responsibility when they fail to exercise adequate supervision and take necessary action against illegal activities occurring within their systems. From the consumer perspective, the impacts are significant, particularly due to limited knowledge, lack of awareness, and insufficient understanding of account legality. Consequently, these conditions contribute to declining public trust in marketplace platforms. In conclusion, the enforcement of legal responsibility for both retailers and marketplace providers is essential to ensure consumer protection and to maintain trust in digital commerce ecosystems.